The Effect of Entrepreneurship Education and Entrepreneurial Mindset on Students' Ability to Innovate with Creativity as a Mediation Variable in the Entrepreneurial Independence Program of Jakarta State University - Ahmad Saoki Andriyana; Dedi Purwana; Suparno (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyses the impact of entrepreneurship education and entrepreneurial mindset on students' innovation capacity, with creativity as a mediating variable. A quantitative approach with an interpretive style was used. Data were collected through questionnaires distributed to 150 undergraduate students participating in the Wira Wiri program at various universities in Indonesia. The data were analysed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that entrepreneurship education has a positive and significant effect on both entrepreneurial mindset and creativity. Furthermore, entrepreneurial mindset significantly influences creativity. Creativity, in turn, has a direct effect on innovation capability. Both entrepreneurship education and entrepreneurial mindset also exhibit direct effects on students' innovation capability. Additionally, creativity is proven to act as a significant partial mediator in the relationship between the independent variables and innovation capability. These findings underscore the importance of strengthening entrepreneurship education and fostering an entrepreneurial mindset to enhance students' creativity and innovation within higher education environments.